2014
DOI: 10.1124/dmd.114.059394
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Coordinated Regulation of KEAP1-NRF2-ARE and p53/p21 Signaling Pathways Is Associated with Acetaminophen Injury Responsive Liver Regeneration

Abstract: Acetaminophen (APAP) overdose is the leading cause of druginduced liver injury. Compensatory liver regeneration is crucial for the final outcome of toxicant-induced injury. However, the molecular mechanisms underlying compensatory liver regeneration in mice after APAP-induced liver injury are not completely understood. This study aimed to investigate the role of dynamic and coordinated regulation of Kelch-like ECH-associated protein 1 (KEAP1)-nuclear factor erythroid 2-related factor 2 (NRF2)-antioxidant respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…Similar observations were made in murine T organoids bearing sh Nrf2 (Figure 5B). This is consistent with earlier reports showing a correlation between the expression of Nrf2 and some of these proteins (Fan et al, 2014; Ke et al, 2013; Malec et al, 2010; Niture and Jaiswal, 2012; Wang et al, 2016). Quantitative PCR of polysome fractions revealed an increase in the association of the mRNAs of these proteins with the translationally inactive monosome fractions (Figure 5C), while no differences were seen for Actin, Mcl-1, and interestingly, Bcl2 mRNAs (Figure S5B).…”
Section: Resultssupporting
confidence: 94%
“…Similar observations were made in murine T organoids bearing sh Nrf2 (Figure 5B). This is consistent with earlier reports showing a correlation between the expression of Nrf2 and some of these proteins (Fan et al, 2014; Ke et al, 2013; Malec et al, 2010; Niture and Jaiswal, 2012; Wang et al, 2016). Quantitative PCR of polysome fractions revealed an increase in the association of the mRNAs of these proteins with the translationally inactive monosome fractions (Figure 5C), while no differences were seen for Actin, Mcl-1, and interestingly, Bcl2 mRNAs (Figure S5B).…”
Section: Resultssupporting
confidence: 94%
“…2A). Compared with the first 24 hours, much less hepatocellular injury and necrosis was observed at 48 hours but was not yet completely resolved consistent with a previous report (Fan et al, 2014a). Treatment with WZ24 hours after NAC dosing, which was not observed in APAP-treated and APAP/WZ-treated mice.…”
Section: Resultssupporting
confidence: 78%
“…In a previous study, the p53/p21 signaling pathway was reported to participate in compensatory liver regeneration after APAP-induced liver injury (Fan et al, 2014a). Thus, p53 and p21 protein expression was investigated to explore whether WZ or NAC could block p53/p21 signaling to promote liver repair in mice after APAP-induced toxicity.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Several studies have shown that acute liver injury induced by moderate doses of APAP is a dynamic process including initiation of injury, progression of injury, and compensatory liver repair (Mehendale, 2005;Bajt et al, 2008;Fan et al, 2014). In the present study, WZ suppresses NAPQI generation required for initiating cellular toxicity through inhibition of P450 enzyme activities and induction of UGT, sulfotransferase, and multidrug resistance-associated protein expression and prevents oxidative stress induced progression of liver injury by activating the NRF2-ARE pathway.…”
Section: Discussionmentioning
confidence: 66%